Cloning of Pf3, a filamentous bacteriophage of Pseudomonas aeruginosa, into the pBD214 vector of Bacillus subtilis. - Putterman, D G (1983)
The genome of Pf3, a filamentous single-stranded DNA bacteriophage of Pseudomonas aeruginosa (a gram-negative organism) was cloned into pBD214, a plasmid cloning vector of Bacillus subtilis (a gram-positive organism). Cloning in the gram-positive organism was done to avoid anticipated lethal effects. The entire Pf3 genome was inserted in each orientation at a unique Bc/I site within a thymidylate synthetase gene (from B. subtilis phage beta 22) on the plasmid. Additional clones were made by inserting EcoRI fragments of Pf3 DNA into a unique EcoRI site within this gene.